MANAGEMENT OF BENIGN PROSTATIC HYPERPLASIA (GRADE I & II) BY PHYTOTHERAPY (International Journal of Ayurveda and Pharma Research, 2017)
Benign prostatic hypertrophy (B.P.H) is a common condition in men above 50 years of age & is characterized by a non malignant enlargement of the prostate resulting from excessive cellular growth of both the glandular and the stromal elements of the gland. The clinical feature of B.P.H. includes incomplete emptying, frequency, intermittency, weak stream, straining & nocturea. Modern treatment though effective in treating symptoms has a number of side effects such as Sexual dysfunction, Postural hypotension, Asthenia and Dizziness etc. Similarly, surgical procedures such as prostatectomy, laser treatment & transurethral resection of the prostate (TURP) are costly & associated with a high risk of complications and morbidity. Hence, there is definite need to explore and evaluate the efficacy of Ayurvedic medicines in the management of B.P.H.This B.P.H can be correlated with Vata-ashthila, described by Sushruta. Herbal drugs mentioned in the management of Vata-ashthila not only take care of symptoms but also aims to break the pathology & improves quality of life of patient. So, this clinical study was done to establish an Ayurvedic conservative treatment for B.P.H – Grade I & II, which is cost effective, free from adverse reactions and side effects of Allopathic drugs.An open randomized controlled clinical trial was conducted with Group A (phytotherapy) comprised of Ghana of Ashwagandha, Varun, Gokshur, Haritaki & Punarnava, whereas, in Group B -a 1 blocker (Tamsulosin hydrochloride) was selected.The comparative analysis of results in both Group-A & B, revealed that the total effect of the therapy was same in both the groups. In Group A, 26.66% patients were Cured, 63.33% were relieved, 10% patients were markedly improved. Similarly, in Group B, 30% patients were Cured, 66.66% were relieved, 3.33% patients were markedly improved. This proves that the Phytotherapy combination does give the patients the same expected relief like modern drug i.e. Tamsulosin hydrochloride.